Carbon stock in the development of different designs of biodiverse agroforestry systems - Cinira de A. F. Fernandes; Sylvana N. Matsumoto; Volney S. Fernandes (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to estimate the carbon stock in the different designs of biodiverse agroforestry systems (AFSs) in the region of the Environmental Protection Area (EPA) of Pratigi, Bahia, Brazil. Phytosociology aspects related to the potentiality of carbon stock of 10 farms were evaluated using plots of 10 x 50 m allocated in each AFS, inventorying 928 individuals of 17 families and 37 species, established in 2013. The biomass above and below the soil of the arboreal individuals were estimated by indirect method, using specific allometric equations for each species or group of species, with diameter above 1 cm. Carbon stock (CS) was estimated from the biomass. Cacao (Theobroma cacao) and rubber tree (Hevea brasiliensis) were the dominant species in all of the designs, which also contained fruit trees, and native and exotic shade trees. There was variation of the estimate of carbon stock (8.01-1.42 Mg ha-1) between the types of AFSs. The designs with a larger relative density of fruit and shade trees led to larger carbon storage, influenced by the wealth and diversity of species in the initial phase of establishment of biodiverse AFSs.